DC-159a Shows Inhibitory Activity against DNA Gyrases of Mycobacterium leprae. - Tomoyuki Yamaguchi; Kazumasa Yokoyama; Chie Nakajima; Yasuhiko Suzuki (PLoS Neglected Tropical Diseases, 2016)
BACKGROUND:Fluoroquinolones are a class of antibacterial agents used for leprosy treatment. Some new fluoroquinolones have been attracting interest due to their remarkable potency that is reportedly better than that of ofloxacin, the fluoroquinolone currently recommended for treatment of leprosy. For example, DC-159a, a recently developed 8-methoxy fluoroquinolone, has been found to be highly potent against various bacterial species. Nonetheless, the efficacy of DC-159a against Mycobacterium leprae is yet to be examined. METHODOLOGY/PRINCIPAL FINDINGS:To gather data that can support highly effective fluoroquinolones as candidates for new remedies for leprosy treatment, we conducted in vitro assays to assess and compare the inhibitory activities of DC-159a and two fluoroquinolones that are already known to be more effective against M. leprae than ofloxacin. The fluoroquinolone-inhibited DNA supercoiling assay using recombinant DNA gyrases of wild type and ofloxacin-resistant M. leprae revealed that inhibitory activities of DC-159a and sitafloxacin were at most 9.8- and 11.9-fold higher than moxifloxacin. Also the fluoroquinolone-mediated cleavage assay showed that potencies of those drugs were at most 13.5- and 9.8-fold higher than moxifloxacin. In addition, these two drugs retained their inhibitory activities even against DNA gyrases of ofloxacin-resistant M. leprae. CONCLUSIONS/SIGNIFICANCE:The results indicated that DC-159a and sitafloxacin are more effective against wild type and mutant M. leprae DNA gyrases than moxifloxacin, suggesting that these antibacterial drugs can be good candidates that may supersede current fluoroquinolone remedies. DC-159a in particular is very promising because it is classified in a subgroup of fluoroquinolones that is known to be less likely to cause adverse effects. Our results implied that DC-159a is well worth further investigation to ascertain its in vivo effectiveness and clinical safety for humans.